Agronomic evaluation of a collection of the tropical pasture Chloris gayana for year round forage supply in a dry sub-humid environment in Córdoba, Colombia - Mejía, Sergio; Tapia, Jose; Sotelo, Mauricio E.; Arango, Jacobo; Peters, Michael (International Center for Tropical Agriculture, 2019)
Worldwide, about 3,400 million hectares are used for feeding livestock, often on natural or naturalized pastures with seasonal feed shortages mainly due to lack of water